2005
DOI: 10.1029/2003je002214
|View full text |Cite
|
Sign up to set email alerts
|

Comparing landslides to fluidized crater ejecta on Mars

Abstract: [1] We use the Mars Global Surveyor and Viking data sets to compare and contrast the geomorphology of four large Martian landslides located in Valles Marineris to fluidized ejecta of seven fresh Martian craters located in Lunae Planum. Both mass movements have flowed over the Martian surface and possess characteristics seen in terrestrial mass movements. We combine these comparisons with simple flow models to determine how the planar geometry of landslides and the cylindrical geometry of ejecta can generate di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
95
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(102 citation statements)
references
References 78 publications
(185 reference statements)
7
95
0
Order By: Relevance
“…Baloga et al (2005) constructed a basic continuum flow model for the emplacement of the distal rampart deposits on Mars. This model extends the approach used in Barnouin-Jha et al (2005) by postulating an independent description of momentum conservation during transit. They found that three factors led to the formation of sharp distal peaks.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Baloga et al (2005) constructed a basic continuum flow model for the emplacement of the distal rampart deposits on Mars. This model extends the approach used in Barnouin-Jha et al (2005) by postulating an independent description of momentum conservation during transit. They found that three factors led to the formation of sharp distal peaks.…”
Section: Introductionmentioning
confidence: 99%
“…The alternative ideathat fluid flow of the ejecta was due to strong winds generated by impact-comes from the similarity in appearance between fluidized crater ejecta seen on Mars and flow generated in the presence of an atmosphere in the laboratory (Schultz andGault 1979, 1982;Schultz 1992). The possibility that fluidized ejecta are the result of dry granular flows that do not require any fluidizing agent is also a possibility (Barnouin-Jha 2005;Barnouin-Jha et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibilities for the role of the atmosphere range from significant, near-rim entrainment in vortices to post-ballistic processes such as gas entrainment in flows and recovery winds scouring the postemplacement surface (Schultz and Gault 1979;Schultz 1992a;Schultz 1996, 1998). Involvement of subsurface volatiles could range from producing mud flows that originate near the rim to providing lubrication for flows that essentially begin after lunar-like ballistic deposition (e.g., Carr et al 1977;Gault and Greeley 1978;Barnouin-Jha et al 2005). While these mechanisms will all produce radially symmetric ejecta blankets for near-vertical impacts, clearly the nature of the asymmetries with oblique impact will vary between mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…They have long run-out distances that usually exceed the run-out of ejecta seen on other planets (Schultz and Singer 1980;Schultz 1992), and the distal deposits beyond the near-rim region are on average fairly thin (50-100 m) (Barnouin-Jha et al 2005a;Baloga et al 2005). They often possess one or more ramparts, which can measure ~200 m in height, at their edges (Barnouin-Jha et al 2005a;Baloga et al 2005).…”
Section: Introductionmentioning
confidence: 99%